(3GdLdjS GdUGdM GdcGaj hGdCfjS GdfGUM GdTGajs - (3GdeYGaj Hf RcQjG Hf jMji GdLQjQqj GdfgQhGfj, nCoHh GdnanQL GHf WQGQ,J (B390 (3g` s
(3BNQgG (B:s
(3jfJgi Edi BNQ GdeLdS GdMGOi hGdYTQjf s
(3fSNI SGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B302s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B441 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B593s
Keywords: (3GdCOHs